The Translation Strategies of Rhyming Utterances in J.K Rowling’s Novel The Christmas Pig - Bahadi, Camelia (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This article discusses the translation strategies of rhyming utterances in the children’s novel entitled The Christmas Pig by J.K Rowling from English into Indonesian. The aim is to describe the translation strategies used in the translation of the novel. The method used is qualitative descriptive, and the data is analyzed using translation strategies proposed by several experts. The results show that the translation strategies used in translating rhyming utterances in The Christmas Pig novel include modulation, calque or literal translation, transposition, descriptive equivalence, translation with generic or more general words, translation with addition, and translation with reduction. This article can be useful for translators in understanding the appropriate translation strategies when translating rhyming utterances in children’s novels.